The influence of formation temperatures on the crystal structure and mechanical properties of ultrahigh-molecular-weight polyethylene/high-density polyethylene-blend fibers prepared by melt spinning. (March 2020) - Wang, Fei; Liu, Lichao; Xue, Ping; Jia, Mingyin; Wang, Suwei; Cai, Jianchen
The influence of spinning temperature on ultrahigh-molecular-weight polyethylene/high-density polyethylene as-spun blend filaments and the influence of drawing temperature on ultrahigh-molecular-weight polyethylene/high-density polyethylene-blend fibers were investigated. The results showed that the optimum spinning and hot-drawing temperatures were 310℃ and 85℃, respectively, and blending with high-density polyethylene improved the orienting ability of the molecular chains and the crystallization ability. The blend filaments spun at 310℃ had the best molecular chain orientation, crystallinity and crystal orientation of the filaments examined; both lower and higher spinning temperatures were detrimental to the crystal structure growth of the as-spun blend filaments. The optimum drawing temperature of the blend fibers was 85℃, which resulted in blend fibers with the best molecular chain orientation, crystallization, and crystal orientation as well as the thinnest grains of the fibers examined. The highest tensile strength and initial modulus were 1204 MPa and 20.4 GPa, respectively; these high values can be attributed to the fibrillar structure, which consisted of extended molecular chains and thin grains. The results in this paper can help disclose the effect mechanism of formation temperature on the melt spinning method used to produce high-strength ultrahigh-molecular-weight polyethylene fibers.